Supernova remnants on the outskirts of the Large Magellanic Cloud - Sasaki, Manami; Zangrandi, Federico; Filipović, Miroslav; Alsaberi, Rami Z.E.; Collier, Jordan D.; Haberl, Frank; Heywood, Ian; Kavanagh, Patrick; Koribalski, Bärbel; Kothes, Roland; Lazarević, Sanja; Maggi, Pierre; et al. (Astronomy & Astrophysics, 2025)
When a star dies, it can explode in a supernova, causing a strong shock wave and forming an interstellar object called a supernova remnant (SNR). Observational studies of SNRs allow us to learn about the different types of progenitors, the explosion mechanisms, the physics of interstellar shocks, and the matter cycle in galaxies. We report on the first detection of SNRs located on the outskirts of a galaxy; namely, the Large Magellanic Cloud (LMC), the largest satellite galaxy of our Galaxy. The sources were discovered ∼3 outside the main stellar and gas distribution of the LMC in the recent surveys in radio with the Australian Square Kilometre Array Pathfinder (ASKAP) and in X-rays with the extended Roentgen Survey with an Imaging Telescope Array (eROSITA). We studied them in follow-up observations with the X-ray Multi-Mirror Mission-Newton telescope and MeerKAT and confirmed them to be SNRs. Their progenitors are most likely stars that had left the LMC due to tidal interaction between the Magellanic Clouds and the Milky Way. SNR J0614-7251 is located in an environment with a similar density to those of the other known SNRs in the LMC, and has similar X-ray properties. SNR J0624-6948, on the other hand, is located in a region with a lower density, n0 < 0.01 cm-3. Its radio shell shows a spectral index and polarisation typical of an SNR.
CRIS-Team Scopus Importer:2025-02-28
Keywords: ISM: supernova remnants; Magellanic Clouds; X-rays: individuals: SNR J0614-7251; X-rays: individuals: SNR J0624-6948; X-rays: ISM